Challenges and Advances in Tuberculosis and Mycobacterial Lung Diseases - Szturmowicz, Monika; Augustynowicz-Kopeć, Ewa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue of the journal Diagnostics entitled "Challenges and Advances in Tuberculosis and Mycobacterial Lung Diseases" encompasses research articles, case presentations, and literature reviews concerning the epidemiology, medical surveillance, as well as diagnostic and therapeutic challenges in tuberculosis (TB) and in the infections caused by non-tuberculous mycobacteria (NTM ). The articles present the current status of knowledge concerning the use of molecular tests and genotyping of M. tuberculosis for the rapid identification of MDR and XDR clones, the advances in the identification of NTM and their differentiation to the species level, as well as clinical studies performed in TB and NTM risk groups. In addition, a summary of current recommendations concerning diagnosis and treatment of tuberculous pericarditis is presented.